Effects of lemon (Citrus Limon L.), lemongrass (Cymbopogon citratus) and peppermint (Mentha piperita L.) essential oils against of Botrytis cinerea and Penicillium expansum. Issue 8 (25th July 2022) - Kgang, Itumeleng E.; Mathabe, Patricia M. K.; Klein, Ashwil; Kalombo, Lonji; Belay, Zinash A.; Caleb, Oluwafemi James
Abstract: Background: Postharvest pathogens Botrytis cinerea and Penicillium expansum causes significant postharvest deterioration of fresh fruit, resulting in economic losses globally. Essential oils (EOs) are safe fungal biodeterioration alternatives compared to chemical fungicides. The aim of this study was to characterise and evaluate the additive and/or synergetic effects of lemon (Le‐), lemongrass (Lg‐), and peppermint (P‐EOs) against mycelial growth and spore germination of B. cinerea and P. expansum . Results: GC–MS analysis depicted 7, 10 and 10 compounds being the major component for Le‐, Lg‐ and P‐EOs, respectively. Most abundant compound being δ‐limonene (71%), α‐citral (50.1%), and menthyl acetate (48%) in Le‐, Lg‐ and P‐EOs, respectively. In vitro investigation showed significant inhibition against mycelial growth and spore germination of B. cinerea and P. expansum with a MIC of 5 and 10 mg/L, respectively. P. expansum was more susceptible to the EOs compared to B. cinerea. The concentrations causing 50% reduction (EC50 ) in mycelial growth for P. expansum were 4, and 9 mg/L for P‐EO and Le‐EO, respectively. At the lowest concentration (0.62 mg/L), volatile phase treatment for P‐ and Lg‐EOs showed 100% inhibitory effects against all fungal mycelial growth compared to contact phase with ≈30% and 60% inhibitory effects, respectively, against P. expansum . Conclusions: Combination of essential oils showed stronger antifungal efficacy compared to individuals. EOs were more effective in volatile phase than direct contact at low concentrations. This shows the potential of using EOs in fogging treatments.